Cellular solids : structure and properties / Lorna J. Gibson, Michael F. Ashby. - Gibson, Lorna J. (Cambridge solid state science series, 1999)
In this edition of their classic work on cellular solids, the authors have brought the book completely up to date, with new work on processing of metallic & ceramic foams & on the mechanical, electrical & acoustic properties of cellular solids.